2019
DOI: 10.18483/ijsci.2058
|View full text |Cite
|
Sign up to set email alerts
|

Growth Assessment and Microbial Flora Presence in African Catfish (Clarias gariepinus) Larvae Fed Live and Commercial Feeds

Abstract: Assessment was carried on the growth and microbial flora presence in African catfish (Clarias gariepinus) larvae fed with live food(Artemia) and commercial feed (Aller Aqua). Two days old larvae (n=200) of average weight (4.8± 0.01mg)and length (6.16±0.03mm)were reared in triplicates for 21 days in plastic tanks (40cm x 25cm x 25cm) dimension. The experiment was done in 12 hours static and 12 hours flow through periods each day. The physico-chemical parameters were within acceptable range for catfish culture e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Moreover, the quality of the protein could also affect the yield as observed byUmoru et al (2016) when Coppens, Chi and Dizengoff was fed to Clarias gariepinus. The crude protein value of the 3 commercial feeds evaluated in this study were similar to the ranges reported byUmoru et al (2016) andAjayi et al (2016). The mean physicochemical parameters of water in this study were within recommended levels as documented byOmitoyin (2007).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, the quality of the protein could also affect the yield as observed byUmoru et al (2016) when Coppens, Chi and Dizengoff was fed to Clarias gariepinus. The crude protein value of the 3 commercial feeds evaluated in this study were similar to the ranges reported byUmoru et al (2016) andAjayi et al (2016). The mean physicochemical parameters of water in this study were within recommended levels as documented byOmitoyin (2007).…”
supporting
confidence: 90%
“…The proximate composition of the feeds was carried out as described by AOAC (1990). At the end of the experiment the following growth parameters were calculated as described by Ajayi et al (2016). Average feed quantity used (g).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clarias gariepinus is a species of catfish with commendable potential in aquaculture as a result of its fast growth rate, high survival rate, disease resistance, good nutritional profile and good flesh quality. Some of the bottle necks in the aquaculture industry includes non-availability of quality fry, lack of feed and feed materials and poor quality of the aquatic environment [5,6,7]. The above bottle necks exposes catfish to bacterial infections such as Aeromonas hiphoplila and Pseudomonas aeruginosa which has resulted to several diseases leading to high mortality and sever economic loses [8,9,10].…”
Section: Introductionmentioning
confidence: 99%